Analisis faktor-faktor yang mempengaruhi pertumbuhan ekonomi dan tingkat kemiskinan di kabupaten berau - Tety Marini (Faculty of Economics and Business Mulawarman University, 2016)
The purpose of this research is to analyze and determine the effect of education directly to economic growth, to analyze and determine the effect of wages directly to economic growth, to analyze and determine the influence of direct investment to economic growth, to analyze and determine the effect of education directly against poverty, analyze and determine the effect of wages directly to the poverty level to analyze and determine the influence of direct investment on poverty levels, analyze and determine the effect of economic growth directly against poverty, analyze and determine the effect of education indirectly against poverty through economic growth, analyzing and determine the effect of wages indirectly against poverty through economic growth, Analyze and determine the effect of investment indirectly to poverty through economic growth in Berau. Model analysis in this study using a research model path (path analysis). In order to test the hypothesis author analyzes using analytical tools Line by using SPSS 22. The data used in this research is secondary data obtained from the Central Bureau of Statistics is data which consists of education, wages, investment, economic growth and poverty in 2004 up to 2014. The analysis showed that the variables Education variable direct impact, positive but not significant effect on the variables of economic growth, the variable wage direct effect, positive but not significant effect on the variables of economic growth, the variable investment directly affect, positively and significantly to variable economic growth, education variable direct effect, negative and significant effect on poverty variable, variable wage direct effect, negative and significant effect on poverty variable, variable investment directly affect, positively and significantly to poverty variable, variable economic growth directly affect, positively and no significant effect on poverty variable, education variable is not a direct and positive effect on the variable poverty through economic growth, variable pay and a positive indirect effect on variable poverty through economic growth, investment variables are not a direct and positive effect on the variable poverty through economic growth in Berau.Keyword: Analyze and determine the effect of investment indirectly to poverty through economic